Controllable self-assembly of CdS@NH2-MIL-125(Ti) heterostructure with enhanced photodegradation efficiency for organic pollutants through synergistic effect. (July 2019) - Wang, Hang; Cui, Peng-Hui; Shi, Jun-Xia; Tan, Jing-Yi; Zhang, Jian-Yong; Zhang, Na; Zhang, Cheng
Abstract: In this work, we employed solvethermal method to assemble highly crystalline NH2 -MIL-125(Ti) nanocrystals on the CdS nanorods, forming CdS@NH2 -MIL-125(Ti) (S@T-n) heterostructured photocatalyst. The photocatalytic activity, structures and morphology of the composites were characterized by UV–vis diffuse reflectance, powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer–Emmett-Teller (BET), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS). Compared to pristine CdS, the S@T-n composites exhibited enhanced photo-degradation efficiencies for Rhodamine B (RhB), phenol and oxytetracycline (OTC) from aqueous solution under visible-light irradiation. Among them, the S@T-10 composite demonstrated the highest photocatalytic performance, and reached 361.4 times for phenol, and 236 times for OTC of Degussa P-25. The enhancement of photocatalytic activity could be described to the novel heterostructure, which can not only provide abundant surface area for the adsorption and diffusion of organic pollutants, but also efficient visible-light harvesting and interfacial charge separation. The possible photocatalytic mechanism of superoxide (O2 − ) and holes (h + ) by the electron-spin-resonance (ESR) was also investigated detailed.